Research on Information Security Transmission of Port Multi-Thread Equipment Based on Advanced Encryption Standard and Preprocessing Optimization - Zhixin Xia; Xiaolei Yang; Afei Li; Yongshan Liu; Siyuan He (Applied Sciences)
Based on the C/S multithreaded control framework, this article used AES encryption technology, and by customizing the S-boxes therein and differential diffusion of the S-boxes, it improved the randomness of the ciphertexts and the resistance to differential attacks, and reduced the likelihood of leakage in the process of data computation. On this basis, in order to reduce the cost overhead generated by AES encryption, this paper used the pre-computed method of optimizing S-boxes and Mixcolumn matrices to be applied to the multithreaded control framework, which improved the computation rate of AES, and then it improved the efficiency of the information transmission in the multithreaded control process. In addition, by using the TLS protocol, the authentication module was set up on the client and server side, which effectively defended against various attacks on data transmission by external users. The experimental results indicate that after the optimization of the multithreaded C/S architecture, the corresponding time of the average transmission delay was reduced by 49.1%, the throughput rose by 96.4%, and the acceleration ratio reached 1.96.